The Effect of Educational Dietary Approaches to Stop Hypertension on Blood Pressure Changes in the Elderly in the Work Area of the Kutalimbaru Health Center Deli Serdang Regency in 2022 - Lindawati Simorangkir; Agustaria Ginting; Uli Veira (Institute of Computer Science (IOCS), 2022)
Abstract Hypertension is a non-communicable disease if not controlled can lead to complications of stroke and even death. The purpose of this study was to determine the effect of dietary approaches to stop hypertension on changes in blood pressure in the elderly in the work area of ​​the Kutalimbaru Health Center, Deli Serdang Regency in 2022. The research method used correlation with a one group pretest - posttest design. of 31 respondents, with purposive sampling technique. The data was taken directly using the observation sheet. The results of the study found that the mean pretest was 155.15 mm Hg where the standard deviation was 9.616, while the posttest mean was 147.74 mm Hg with a standard deviation of 8.835. The results of the research before and after the DASH intervention was given the Wilcoxon rank test statistical test results obtained a p value of <0.05 where the effect of DASH education on changes in blood pressure in the elderly in the working area of ​​the Kutalimbaru Public Health Center, Deli Serdang Regency in 2022. It is hoped that the results of this study can used as material when conducting education about the DASH diet for people with hypertension when conducting research, especially the elderly at the Kutalimbaru Public Health Center, Deli Serdang Regency because many respondents did not know about the DASH diet pattern